Caracterización edáfica y climática de QUERCUS SUBER L. EN LAS PROVINCIAS DE SALAMANCA Y ZAMORA - JOVELLAR LACAMBRA, L C; A., BLANCO ANDRAY; SANTOS FRANCÉS, F (IV Congreso Forestal Español, 2005)
Ecological parameters characterizing cork oak forest in west-central Spain (Salamanca y Zamora) were obtained. From those parameters, central and marginal habitats for Quercus suber stands were established for this region of Spain. Main soils and climate types for the present sites of these forests have been identified as well
Keywords: Cork Oak Forest; ecology; habitat; Quercus suber; Salamanca; Zamora